Analysis on the relationship between winter precipitation and the annual variation of horse stomach fly community in arid desert steppe, Northwest China (2007–2019). Issue 1 (10th August 2021) - HUANG, Heqing; ZHANG, Ke; ZHANG, Boru; LIU, Shanhui; CHU, Hongjun; QI, Yingjie; ZHANG, Dong; LI, Kai
Abstract: Gasterophilus spp. have been found to be widespread in reintroduced Przewalski's horses in the Kalamaili Nature Reserve (Northwest China). However, data on the annual variation in Gasterophilus infections are lacking. To analyze the epidemiological features and determine the cause of the annual variation in Gasterophilus infections, we treated 110 Przewalski's horses with ivermectin and collected Gasterophilus larvae from fecal samples each winter from 2007 to 2019. All 110 Przewalski's horses studied were found to be infected by Gasterophilus spp., and a total of 141 379 larvae were collected. Six species of Gasterophilus were identified with the following prevalence: G. pecorum (100%), G. nasalis (96.36%), G . nigricornis (94.55%), G. haemorrhoidalis (56.36%), G. intestinalis (59.09%), and G. inermis (3.64%). The mean infection intensity of Gasterophilus spp. larvae in Przewalski's horses was 1285 ± 653. G. pecorum (92.96% ± 6.71%) was the most abundant species. The intensity of Gasterophilus spp. ( r = –0.561, P < 0.046) was significantly correlated with winter precipitation. Our findings confirmed that, in the Kalamaili Nature Reserve, gasterophilosis is a severe parasitic disease in Przewalski's horses. Winter precipitation at the beginning of the year can indirectly affect the intensity and composition of Gasterophilus spp. in Przewalski's horses at the end of the year. Therefore, the water‐related ecological regulation should be carried out to help reduce the parasite infection of Przewalski's horses. Abstract : The botfly infestation intensity of Przewalski's horses were investigated for 13 years in Kalamaili Nature Reserve, China. The intensity and composition of botflies were affected by winter precipitation indirectly in Przewalski's horses. The distribution of artificial water sources sites should be considered for decreasing the intensity of equines during the infection period of botflies.